Analisis Kesehatan Bank Dengan Menggunakan Metode RGEC Pada Pt. Bank Negara Indonesia Persero Tbk - Cicik Vistanika Metara; Ustadus Sholihin; Zulfia Rahmawati (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the health assessment of PT. Bank Negara Indonesia Persero Tbk which has been registered on the IDX is reviewed from the aspects of Risk Profile, Good Corporate Governance, Earnings and Capital. This type of research is quantitative research and uses the RGEC method. From this research, on the Risk Profile which was measured using NPL, the results obtained in 2017, 2018 and 2019 were ranked 1, namely very healthy, in 2020 and 2021 they were ranked 2, namely healthy. In Good Corporate Governance, it has been stable for 5 years, ranking 2, namely good. In Earnings which are measured using Return On Assets, the results obtained in 2017, 2018 and 2019 were ranked 1, namely very healthy, in 2020 they were ranked 3, namely quite healthy, and in 2021 they were ranked 2, namely healthy. In terms of capital, which is measured using the Capital Adequacy Ratio, the consecutive results obtained in 2017, 2018, 2019, 2020 and 2021 were ranked 1, namely very healthy.